Distribution of CD15- and CD31-Positive Cells in the Oesophageal Mucosa of Children With Eosinophilic Oesophagitis Across Different Age and Sex Groups - Demyashkin, Grigory; Shalatonin , Mikhail; Yuferov, Daniil; Thaler, Alexander; Tsibulevsky, Alexandr; Borovaya, Tatyana; Blinov , Kirill; Tuktarova, Amira (Scripta Medica, 2026)
Background/Aim: Eosinophilic oesophagitis (EoE) is a chronic immune-mediated inflammatory disease of the oesophagus with a multifactorial nature. The prognosis and effectiveness of therapy for EoE largely depend on a detailed study of its pathogenetic mechanisms. To clarify the severity of the inflammatory process, along with routine histological methods, a comprehensive immunohistochemical examination of the oesophageal mucosa was performed. To verify the intensity of tissue alterations, the marker CD15 was used and to assess the state of the vascular bed and the degree of vascularisation, the endothelial marker CD31 was employed. The aim of this research was to determine the morphometric features of the inflammatory process and tissue vascularisation in EoE in children of different age and sex groups. Methods: A retrospective study included 94 children with EoE (ICD-10: K20), stratified into three age subgroups: Subgroup A (3–7 years), Subgroup B (8–12 years) and Subgroup C (13–18 years). The study utilised clinical data and morphological methods (general histology, histochemical reactions – Masson's trichrome and Periodic acid–Schiff (PAS) and immunohistochemical analysis for CD15 and CD31) for examining biopsy material from the oesophageal mucosa. Results: Distinct age- and sex-dependent patterns were identified. In male patients, peak CD15+ cell density was recorded in Subgroup A, demonstrating a significant 1.57-fold decrease toward the adolescent group (p < 0.05). Conversely, female patients demonstrated the lowest CD15+ density in Subgroup A, with a significant 1.89-fold increase in Subgroup C (p < 0.05), where female CD15+ density exceeded males by 1.94 times (p < 0.05). All assessed microvascular parameters progressively increased from Subgroup A to C in both sexes (p < 0.05). When comparing by sex in the older age cohort, the microvascular density in girls significantly exceeded that in boys by 1.18 times (p < 0.05).Conclusion: EoE in children is characterised by distinct age- and sex-dependent inflammatory and structural changes in the oesophageal mucosa. Immunohistochemical analysis revealed prominent epithelial CD15 expression reflecting the intensity of cellular alteration and CD31+ endothelial reactivity reflecting a microvascular response during the development of the disease. The results underscore the importance of comprehensive diagnostics, including detailed morphological, histological and immunohistochemical evaluation of the mucosa, which may provide valuable insights for improving diagnostic strategies and monitoring disease progression.
Keywords: Oesophagus; Eosinophilic Oesophagitis; Lewis x antigen; CD15; Platelet endothelial cell adhesion molecule-1; CD31; Child